KATA “NENEN” SEBAGAI MEREK WARUNG: The Word “Nenen” as a Stall Brand - Sinta Anjani Hastaningrum; Aline Gratika Nugrahani (AMICUS CURIAE, 2025)
Trademark registration is done to provide legal protection against the use of trademarks by other parties. Protected trademarks are those that meet the registration requirements in accordance with Article 20 of Law No. 20 Year 2016 on Trademarks and Geographical Indications. However, in reality there are still many applications for trademarks that do not meet these requirements, but the registration is accepted by the Directorate General of Intellectual Property / DJKI so that the trademark is protected and one of them is the ‘Warung Nenen’ trademark. The identification of the research problem is whether the word ‘Nenen’ in the ‘Warung Nenen’ trademark meets the requirements of Article 20 of Law No. 20 of 2016 concerning Trademarks and Geographical Indications, and what is the basis for the DJKI's consideration to approve the registration of the ‘Warung Nenen’ trademark. The research method employed is normative juridical, descriptive in nature, utilizing primary and secondary data collected through interviews and literature studies, and the data are analyzed qualitatively. The conclusion shows that although the word ‘Nenen’ is less ethical/less polite, the registration of the ‘Warung Nenen’ trademark is still accepted by the DJKI as a party that has the authority to examine the trademark.